SOCIO-ECONOMIC MECHANISMS OF USING STRATEGIC MANAGEMENT APPROACHES IN THE DIGITAL ECONOMY (Marketing Journal, 2025)
This article comprehensively analyzes the socio -economic mechanisms of using strategic management approaches in the context of the digital economy. Strategic planning, innovative management approaches, and the integration of modern technologies are considered crucial factors for improving the effectiveness of the digital transformation process. The article also examines the current issues of digital 78 transformation and ways to solve them, using both domestic and international experience, as well as providing practical recommendations for improving socio - economic mechanisms. The research results demonstrate the potential for ensuring the sustainable development of the digital economy through the use of strategic management tools.
Keywords: Digital economy; strategic management; transformation; socio - economic mechanisms; digital technologies; innovative approaches; Uzbekistan; enterprise management; digital transformation; state strategy